2014
DOI: 10.1007/s12185-014-1510-5
|View full text |Cite
|
Sign up to set email alerts
|

Chimerism status is correlated to acute graft-versus-host disease after allogeneic stem cell transplantation

Abstract: To evaluate the correlation between chimerism status and acute graft-versus-host disease (aGVHD) following allogeneic hematopoietic stem cell transplantation. Chimerism of peripheral blood of 124 patients was monitored at regular intervals post-transplant. The chimerism of 124 post-transplant cases of CD3(+)T lymphocytes, 107 cases of CD3(-)CD56(+)CD16(+)NK lymphocytes, 49 cases of CD15(+) granulocytes, and 27 cases of CD19(+)B lymphocytes sorted by fluorescence-activated cell sorter were analyzed by polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…First, residual recipient hematopoiesis after myeloablative conditioning followed by HSCT correlates with graft failure and persisting disease [1,23,24]. Second, achievement of complete donor-derived hematopoiesis early after HSCT is associated with increased incidence of graft-versus-host disease [8,23,25,26]. Last, some studies corroborated a higher risk for disease relapse in patients with mixed recipient chimerism after HSCT [4,5,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, residual recipient hematopoiesis after myeloablative conditioning followed by HSCT correlates with graft failure and persisting disease [1,23,24]. Second, achievement of complete donor-derived hematopoiesis early after HSCT is associated with increased incidence of graft-versus-host disease [8,23,25,26]. Last, some studies corroborated a higher risk for disease relapse in patients with mixed recipient chimerism after HSCT [4,5,27].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data illustrate that the routine assessment of chimerism is a useful approach to evaluate post-transplantation prognosis. Importantly, chimerism status may provide the rationale for post-transplantation therapy like modulation of immunosuppression or donor lymphocyte infusions [8]. Indeed, Bader et al showed that the 3 year event-free survival was increased from 0 to 37% and from 0 to 36% after immunotherapy of patients with increasing recipient chimerism in pediatric ALL [30] and AML [31], respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no significant differences were observed in the occurrence of acute or chronic GvHD between T-cell CDC and MC in the present study, T-cell chimerism may reflect the function of allo-reactivity in not only GVL effect, but also GvHD. Previous studies showed that higher T-cell chimerism was associated with the occurrence of acute GvHD, [10][11][12] chronic GvHD 13 or both. 14 No patient whose T-cell chimerism at day 28 was MC developed grades II-IV acute GvHD in this study.…”
mentioning
confidence: 97%
“…Para a realização desta pesquisa foram analisados um total de (1)(2)(3)(4)(5)(6)(7)(8) é uma abordagem útil para avaliar o prognóstico pós-transplante e influenciar a abordagem terapêutica, como infusões de linfócitos do doador (DLIdonor leukocyte infusion), quimioterapia adicional ou retransplante (9) . Por este motivo, esforços tem sido feito no sentido de aumentar a sensibilidade das técnicas de detecção de quimerismo.…”
Section: Conclusões E Considerações Finaisunclassified